Nonsevere Hemophilia: The Need for a Renewed Focus and Improved Outcomes - Dolan, Gerard; Fijnvandraat, Karin; Lenting, Peter J.; Catarino, Cristina; Lavin, Michelle; on behalf of the Factor Think Tank (Seminars in Thrombosis and Hemostasis, 2024)
People with nonsevere hemophilia (PWNSH) are phenotypically more diverse than those with severe hemophilia. Perceptions relating to a “nonsevere” phenotype have contributed to fewer research initiatives, fewer guidelines on optimal management, and a lack of standards for surveillance and clinical assessment for affected individuals. In many cases, episodes of abnormal bleeding could, if investigated, have led to earlier diagnosis. Furthermore, the major recent developments in therapy for hemophilia have largely focused on severe disease and, as a group, PWNSH have not been included in many key clinical trials. Benefiting people with severe disease, innovative replacement therapies have generally targeted factor levels that are above those present in a large proportion of PWNSH. Therapeutic advances can lead to improvement in phenotype for people with severe hemophilia over that currently experienced by many PWNSH. As a result, we are approaching a point where PWNSH may, in many countries, have a higher risk of bleeding and restriction in lifestyle than those with severe disease but with more limited therapeutic options. Given the multiple major advances in treatment for people with hemophilia, it is timely to review the aspects of nonsevere disease, to ensure equity in care and management for all individuals with this condition.
Keywords: disease management; factor VIII; factor IX; hemophilia A; hemophilia B